Corporate Tax Strategy: Revealing the Influence of Executive Decisions in Tax Avoidance - Ananda, Yovan Allif; Agia, Lintang Nur (Universitas KH. Abdul Chalim Mojokerto, 2026)
The reduction in Indonesia's tax ratio signifies the persistence of tax evasion tactics, especially within the energy industry, characterized by intricate affiliate transactions and substantial financial risks. Transfer pricing and financial suffering are frequently linked to tax evasion; nonetheless, prior research findings remain incongruous. This study seeks to examine the impact of transfer pricing and financial difficulty on tax evasion, with Risk Executive Characteristics serving as a moderating variable. This research employs a quantitative methodology utilizing panel data regression on 62 energy sector firms listed on the Indonesia Stock Exchange from 2022 to 2024. The data was analyzed utilizing EViews 13, employing Cash Tax Evasion (CTA) as a surrogate for tax evasion. The findings indicate that transfer pricing and financial difficulties do not exert a direct influence on tax evasion. Nevertheless, Risk Executive Characteristics enhance the correlation between the two and tax avoidance. This study positions Risk Executive Characteristics as a moderating variable and employs CTA as a more pertinent proxy for assessing tax avoidance.